2011
DOI: 10.4141/cjss10073
|View full text |Cite
|
Sign up to set email alerts
|

Artificial neural network model for estimating the soil temperature

Abstract: Ozturk, M., Salman, O. and Koc, M. 2011. Artificial neural network model for estimating the soil temperature. Can. J. Soil Sci. 91: 551Á562. Although soil temperature is a critically important agricultural and environmental factor, it is typically monitored with low spatial resolution and, as a result, methods are required to estimate soil temperature at locations remote from monitoring stations. In this study, cost-effective, feed-forward artificial neural network (ANN) models are developed and tested for est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Also, ANN is more efficient than the regression methods. Ozturk et al (2011) developed feed-forward ANN models to estimate soil temperature at five depths of 5, 10, 20, 50 and 100 cm in 66 locations of Turkey. They utilized different geographical and meteorological parameters as inputs.…”
Section: Introductionmentioning
confidence: 99%
“…Also, ANN is more efficient than the regression methods. Ozturk et al (2011) developed feed-forward ANN models to estimate soil temperature at five depths of 5, 10, 20, 50 and 100 cm in 66 locations of Turkey. They utilized different geographical and meteorological parameters as inputs.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several studies have reported that the ANN with its ability to model non‐linear relationships may offer a promising alternative for soil temperature modelling. Although several applications of ANNs for this type of modelling exist (George, ; Mihalakakou, ; Bilgili, ; Ozturk et al , ; Tabari et al , ; Bilgili et al , ; Wu et al , ; Hosseinzadeh Talaee, ; Kim and Singh, ; Kisi et al , ), they have so far been restricted to the research environment. The outcomes of such researches are encouraging, as the ANN method has been found to be very useful in providing important information regarding the non‐linear characteristics of soil temperature and its predictability.…”
Section: Introductionmentioning
confidence: 99%
“…ANN is a nonlinear mathematical modeling approach similar by human brain [9]. ANNS have been applying in many researches and various fields of mathematics, engineering, medicine, economics, psychology, neurology, regions Mineralization, in prediction of thermal and electrical [15][16][17][18].…”
Section: Artificial Neural Networkmentioning
confidence: 99%
“…: http://dx.doi.org/10.21839/jaar.2017.v2i5.106 http://www.phoenixpub.org/journals/index.php/jaar ISSN 2519-9412 / © 2017 Phoenix Research Publishers its high efficiency to model non-linear relationships may propose a powerful alternative for soil temperature estimation [8]. Although the results of these researches [8][9][10][11][12][13][14], they still within the research environment. The results of these studies are promising and encouraging, several of mentioned researches employed meteorological data as inputs for the ANN Algorithms, except [11]who predicted soil temperatures of a base station employing soil temperatures of neighbor stations as a unique input parameter without any employing of the other meteorological parameters or elements related to soil properties.…”
Section: Introductionmentioning
confidence: 99%